2023
DOI: 10.3390/s23115251
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Tear Fluid and Its Processing for the Diagnosis of Multiple Sclerosis

Abstract: A pilot analysis of the tear fluid of patients with multiple sclerosis (MS) collected by glass microcapillary was performed using various experimental methods: liquid chromatography–mass spectrometry, Raman spectroscopy, infrared spectroscopy, and atomic-force microscopy. Infrared spectroscopy found no significant difference between the tear fluid of MS patients and the control spectra; all three significant peaks were located at around the same positions. Raman analysis showed differences between the spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…The tear film is part of the ocular surface microenvironement and helps maintaining its homeostasis by providing specific trophic factors to the epithelial surface. Furthermore, the modulation of the tear film composition reflects modification of corneal physiology 45,47,48 . Our proteomic results strongly suggested that the tear film was not affected by the OPA1 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The tear film is part of the ocular surface microenvironement and helps maintaining its homeostasis by providing specific trophic factors to the epithelial surface. Furthermore, the modulation of the tear film composition reflects modification of corneal physiology 45,47,48 . Our proteomic results strongly suggested that the tear film was not affected by the OPA1 mutation.…”
Section: Discussionmentioning
confidence: 99%